2015
DOI: 10.1039/c4nr06371f
|View full text |Cite
|
Sign up to set email alerts
|

Surface-confined 2D polymerization of a brominated copper-tetraphenylporphyrin on Au(111)

Abstract: A coupling-limited approach for the Ullmann reaction-like on-surface synthesis of a two-dimensional covalent organic network starting from a halogenated metallo-porphyrin is demonstrated. Copper-octabromo-tetraphenylporphyrin molecules can diffuse and self-assemble when adsorbed on the inert Au(111) surface. Splitting-off of bromine atoms bonded at the macrocyclic core of the porphyrin starts at room temperature after the deposition and is monitored by X-ray photoelectron spectroscopy for different annealing s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 54 publications
10
51
0
Order By: Relevance
“…Due to sterical hindrance, the reaction did not result in C-C bonds between the β-positions of the porphyrin cores. Instead, C-C bonds were formed between the β-positions and C atoms of the phenyl rings after annealing to 573 K, indicating that also partial dehydrogenation of the phenyl rings occurred [489]. Note that C-C bond formation on the basis of surface-assisted dehalogenation of aromatic bromo-or iodocompounds (also referred to as Ullmann coupling) has also been studied with numerous non-porphyrinic compounds [485][486][487][488].…”
Section: Covalent Networkmentioning
confidence: 95%
“…Due to sterical hindrance, the reaction did not result in C-C bonds between the β-positions of the porphyrin cores. Instead, C-C bonds were formed between the β-positions and C atoms of the phenyl rings after annealing to 573 K, indicating that also partial dehydrogenation of the phenyl rings occurred [489]. Note that C-C bond formation on the basis of surface-assisted dehalogenation of aromatic bromo-or iodocompounds (also referred to as Ullmann coupling) has also been studied with numerous non-porphyrinic compounds [485][486][487][488].…”
Section: Covalent Networkmentioning
confidence: 95%
“…In our study C1 is observed at 284.5 eV and C2 at 285.6 eV and similar values were reported previously . Further, going from CAP to MG the binding energy increases from 284.3 eV to 284.5 eV, which confirms the formation of large carbon networks …”
Section: Resultsmentioning
confidence: 58%
“…The CAP was subjected to Scholl oxidation in 2:1 AlCl 3 ‐NaCl melt at 165 °C for 6 h. The reaction mixture was quenched with water and worked up to get MG in good yields (see supporting information (SI) for details of synthesis). We have applied a variety of techniques (FTIR, UV‐Vis, XPS, Raman, XRD, TEM and AFM) for characterization of the product, and the data obtained were compared with literature to confirm our assignment of the product as graphene sheets.…”
Section: Resultsmentioning
confidence: 99%
“…Four major binding energy peaks were detected at approximately 71, 233, 284, and 533 eV, which were attributed to the Br 3d, Mo 3d, C 1s, and O 1s core levels, respectively. A high‐resolution Br 3d XPS spectrum (Figure b) shows peaks at 68.5, 69.7, and 70.5 eV, which represent covalent bonding (C−Br 3d 3/2 , 56.8%), ionic bonding (C−Br + −C 3d 5/2 , 6.5%), and covalent bonding (C−Br 3d 5/2 , 37.7%), respectively . The existence of ionic bonds could be an important feature for enhancing the electroactivity because these bonds play a vital role as electron donors or acceptors in charge transfer between carbon atoms.…”
Section: Resultsmentioning
confidence: 99%
“…The data clearly show that the series resistance of the devices increases continuously with increasing MoO 3 concentration. The reason is the insulating nature of MoO 3 , which tends to reduce the device efficiency . However, the device with a hybrid HTM having a MoO 3 concentration of 0.2 wt% shows the best efficiency because of the small MoO 3 concentration.…”
Section: Resultsmentioning
confidence: 99%